Law Enforcement in The Process of Investigation on The Crime of Skimming by Foreign Nationals - Chandra Satriana, I Made Wahyu; Dewi, Ni Made Liana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 1 (2022), 2022)
This study aims to analyze the law enforcement process at the level of investigation of skimming crimes by foreign nationals in the jurisdiction of the Bali Police; and Factors that support and hinder the law enforcement process at the investigation level of skimming crimes by foreign nationals in the jurisdiction of the Bali Regional Police. The research method used is a empirical legal research. The results showed that law enforcement process at the level of investigation of skimming crimes by foreign nationals in the Bali Regional Police jurisdiction was carried out based on Perkap No. 6 of 2019 which includes receiving police reports, making investigative administrations, examining victims and witnesses, collecting evidence and conducting case titles that end in the examination process in court; and factors that support and hinder the law enforcement process at the level of investigation of skimming crimes by foreign nationals in the Bali Regional Police jurisdiction, including (a) supporting factors which include their own legal (act factors) and public factors; (b) inhibiting factors include legal themselves (statutory factors), law enforcement, and facilities that support law enforcement, community and legal culture factors.